Sustainability of Microfinance Institutions: An Analysis of Influencing Factors in South Sumatra Province - Ariodillah Hidayat; Suhel Suhel; Mardalena Mardalena (Department of Development Economics, Universitas Sriwijaya, 2023)
Microfinance has become an important tool for poverty alleviation in many countries and the Indonesian government through various intervention programs to overcome poverty has also implemented microfinance programs in Indonesia, one of which is through the Kota Tanpa Kumuh (Kotaku) Program. This study aims to analyze the factors that affect the sustainability of the Financial Management Unit (UPK) Microfinance Institutions (MFI) operating in South Sumatra Province. The purpose of this study is to gain a better understanding of these factors and their sustainability so that they can provide recommendations to stakeholders at both the central and regional levels. The data collection method was used by surveying 50 samples of the UPK Community Self-Reliance Agency (BKM) spread across three cities, namely Palembang City, Prabumulih City and Lubuk linggau City which is the largest city there are UPK BKM microfinance institutions from 7 cities and districts intervened in the Province South Sumatra. The analytical method in this study uses logistic regression to analyze data using descriptive qualitative analysis to explain the factors that influence the sustainability of UPK BKM Microfinance Institutions (MFI) in South Sumatra Province. The results showed that the factors that had a significant effect on the level of sustainability of MFI were BKM support and portfolios at risk.